The Impact of Financial Regulation on the Development of Distributed Ledger Technology (DLT) Firms - Hashimy, Loha; Sandner, Philipp (Frontiers in Blockchain, 2020)
There is disagreement in the literature concerning the impact of regulations on firms’ development. While some researchers believe that regulation impedes companies’ development (Poel et al., 2014; Jalilian et al., 2007), others argue that regulations enable companies’ development (Peck et al., 2018; Mayson et al., 2014). This paper aims to contribute to a better understanding of the impact of financial regulations on development of Distributed Ledger Technology (DLT) firms. In-depth semi-structured open-ended interviews have been conducted with 20 Small Medium Enterprise (SME) DLT companies in Europe during April and May 2019. Our results show that the expected impact of financial regulation can be ambiguous as it can both enable and constrain a firm’s development. This is in line with Kitching et al. (2015) theory of regulation as a dynamic force.